THE EFFECT OF PROMOTION STRATEGIES, PRODUCT, AND DISTRIBUTION ON CONSUMER BUYING INTEREST AT PT. UGGAS SEJAHTERA BERSAMA BRANCH LAMONGAN - Elsa Dwi Rachmadhani; Mohammad Yaskun; Yunni Rusmawati DJ (Sean Institute, 2023)
This research aims to find out the factors about marketing that consist of promotion strategies, product and distribution that can affect consumer buying interest. To find out the effect or absence of independent variables (promotion strategies, product, and distribution) on dependent variables (consumer buying interest) used quantitative research types using questionnaire data, tables and numbers described with appropriate theories and formulas so that valid results are obtained . Based on the results of the analysis conducted, it is known that the promotion strategy variable has a partial effect on the consumer buying interest variable PT. USB. Second, product variables have a partial effect on consumer buying interest variables in PT. USB. Third, the distribution variable has a partial effect on the consumer buying interest variable in PT. USB. It is known that the variables of promotional strategies, products and distributions have a simultaneous effect on the consumer buying interest of PT. USB. From the results of the t test analysis, it is known that product variables have the most dominant influence on consumer buying interest variables in PT. USB.